An Epitaxial Ferroelectric ScAlN/GaN Heterostructure Memory. (15th March 2022) - Wang, Ding; Wang, Ping; Mondal, Shubham; Mohanty, Subhajit; Ma, Tao; Ahmadi, Elaheh; Mi, Zetian
Abstract: Electrically switchable bistable conductance that occurs in ferroelectric materials has attracted growing interest due to its promising applications in data storage and in‐memory computing. Sc‐alloyed III‐nitrides have emerged as a new class of ferroelectrics, which not only enable seamless integration with III‐nitride technology but also provide an alternative solution for CMOS back end of line integration. In this paper, the resistive switching behavior and memory effect in an ultrawide‐bandgap, high Curie temperature, fully epitaxial ferroelectric ScAlN/GaN heterostructure is reported for the first time. The structure exhibits robust ON and OFF states that last for months at room temperature with rectifying ratios of 60–210, and further shows stable operation at high temperatures (≈670 K) that are close to or even above the Curie temperature of most conventional ferroelectrics. Detailed studies suggest that the underlying mechanism is directly related to a ferroelectric field effect induced charge reconstruction at the hetero‐interface. The robust resistive switching landscape and the electrical polarization engineering capability in the polar heterostructure, together with the promise to integrate with both silicon and GaN technologies, can pave the way for next‐generation memristors and further enable a broad range of multifunctional and cross‐field applications. Abstract : Direct growth of ferroelectrics on III‐nitride semiconductors by molecular beam epitaxy and the memory effect in epitaxial ScAlN/GaN heterostructures is demonstrated. The structure exhibits robust ON/OFF states at room temperature and stable resistive switching even at high temperatures. The results could pave the way for next‐generation memristors and enable a broad range of multifunctional and cross‐field applications based on III‐nitrides.